Genome‐wide association with delayed puberty in swine. (26th August 2013) - Nonneman, D.; Lents, C.; Rohrer, G.; Rempel, L.; Vallet, J.
Summary An improvement in the proportion of gilts entering the herd that farrow a litter would increase overall herd performance and profitability. A significant proportion (10–30%) of gilts that enter the herd never farrow a litter; reproductive reasons account for approximately a third of gilt removals, with anestrous and failure to conceive the most common reasons for culling. Tools to select gilts for reproductive longevity through genomics or alternative phenotypes would be of great benefit to the producer. Ninety‐one gilts that failed to display behavioral estrus by 240 days (cases) and 127 pubertal littermates (controls) were genotyped with the Illumina Porcine SNP60 Beadchip. One hundred and seventy‐four SNPs with the most significant associations were genotyped in an additional 86 cases and 103 controls. Twelve of these associations were significant in the final analysis. The most significant (P < 1.5 × 10−14) region associated with failure to attain puberty was on chromosome 4 surrounding the NHLH2 gene. Delayed pubertal development and age at first estrus have been associated with NHLH2 in mice. Because attainment of puberty is a complex trait, identifying genes that affect pubertal age would greatly contribute to our knowledge of reproductive development as well as overall fertility.